ESSENTIAL ROLE OF LANGUAGE LABORATORY TO ENHANCE NAUTICAL SCIENCE STUDENT’S COMMUNICATION ABILITY IN MARITIME ACADEMY OF YOGYAKARTA - Sri Sartini (Sekolah Tinggi Maritim Yogyakarta, 2016)
In the English Language Teaching (ELT) process, the four basic skills of reading, writing, speaking, and listening should be drilled continuosly to get the maximum goal of English learning objective. However, mostly the lecturer or the teacher could not concern to the development of those skills due to some constraints. Classroom factor, strategy factor, student’s factor, lecturer’s factor may hamper the development of those skills at once. Regarding the curriculum, mostly lecturer will catch up to student’s writing skill which involves the mastery of grammatical knowledge and reading competence at class. Somehow, the important of the development of speaking and listening or communication ability is neglected. This research focusses to find the essential role of language laboratory to enhance student’s communication ability. It is hoped that the use of laboratory facility will enable and help lecturer or teacher to highlight their student’s communication ability as well not only their writing and reading skills as a whole. This study applies descriptive qualitative method and It uses theory of Wallace (1991) to analyze the data. The research is conducted in Yogyakarta Maritime Academy. The respondents are the the students of nautical science semester II of Academic year 2015/2016. The key instrument in this research is the researcher herself. Researcher collects the data by observing the teaching-learning process of English class in laboratory several times and then conducts twice in-depth interviews with the students at the end of the class. The data is analyzed through categorization based on the continuous comparison technique. To get the trustworthiness, researcher uses triangulation technique. The result of the research shows that through the abundant variety of teaching technique and media as well as the facilities offered by language laboratory, it could give improtant role in the development of student’s speaking skill or student’s communication ability compared to the use of facilities in the classical room usage..